(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
In Ayurveda classics Mukhadooshika is explained under the context of Kshudra Rogas featuring the formation of Shalamalikantakavat Pidaka. An analogous disorder to Mukhadooshika is Acne Vulgaris, which is a disease of pilosebaceous unit that causes inflammatory and non-inflammatory lesions and varies degree of scarring. Topical applications have been given significance in Ayurveda therapeutics and its emphasis is seen in classical texts. Many Lepa are mentioned in Ayurveda pharmaceutics for the treatment of Mukhadhooshika. One among them is Mukhadooshikahara Lepa mentioned in Sushrutha Samhita Kshudrarogachikitsa Adhyaya. Here an attempt is made to compile the information about this combination.